The impact of obesity and weight loss treatment on metabolic parameters, cardiovascular autonomic and sensory nerve function and in vitro fertilization outcomes in infertile women: a pilot study - Vágvölgyi, Anna; Vedelek, Viktor; Keller, Nóra; Szöllősi, Dalma; Lada, Szilvia; Nemes, Attila; Kempler, Péter; Menyhárt, Adrienn; Baczkó, István; Várkonyi, Tamás; Lengyel, Csaba; Zádori, János (Frontiers in Endocrinology, 2025)
IntroductionThe global rise in obesity is linked to metabolic disorders, such as neuropathy and infertility. Our study aimed to analyze the effects of preconceptional weight loss in infertile women with obesity on peripheral sensory and cardiovascular autonomic nerve function, metabolic parameters, and the success of in vitro fertilization (IVF).MethodsA retrospective cohort study included women with obesity and infertility undergoing weight optimization before IVF, alongside age-matched controls. Clinical and laboratory parameters, cardiovascular autonomic and peripheral sensory function, and body composition were evaluated before and following weight loss therapy.ResultsPatients with obesity [n=58; mean ± SD; age: 33.1 ± 5.42 years; body mass index (BMI): 39.3 ± 6.90 kg/m2] had higher resting blood pressure, prevalence of metabolic disorders, and medication usage than controls (n=45; age: 32.1 ± 7.67 years; BMI: 21.1 ± 2.02 kg/m²). Laboratory findings indicated differences in blood cell counts, glucose metabolism markers, kidney and liver functions, and lipid profile between the groups. Cardiovascular autonomic function tests indicated impairment in Valsalva-ratio (1.4 ± 0.22 vs. 1.5 ± 0.23, p<0.001) and 30/15 ratio (1.07 ± 0.12 vs. 1.12 ± 0.13, p<0.05) in patients with obesity. Peripheral sensory function tests revealed significant deterioration in vibration sense and the current perception threshold of the median nerve at 2000 Hz in patients with obesity, as compared to controls. Before and following weight loss therapy no statistically significant difference was found on cardiovascular autonomic and peripheral sensory function. Following weight loss therapy with lifestyle/dietary intervention and liraglutide, 16 female patients with obesity attended the follow-up measurement. They achieved significant weight reduction (104.3 ± 16.64 vs. 89.1 ± 15.74 kg; p<0.05) and 8 became pregnant (5 via IVF, 3 spontaneously).ConclusionPeripheral sensory neuronal impairments were detected in infertile women with obesity compared to the controls with normal BMI. Cardiovascular autonomic dysfunction was revealed by 30/15 and Valsalva-ratio in patients with obesity, suggesting the presence of parasympathetic dysfunction. Preconceptional weight loss improved metabolic parameters. Of the infertile female patients with obesity who reached their preconceptional target weight, 18.75% achieved spontaneous pregnancy without IVF, and 62.5% of those who underwent IVF successfully conceived.